ON THE RELEVANCE OF BIG DATA FOR THE FORMATION OF CONTRACTS REGARDING PACKAGE TOURS OR LINKED TRAVEL ARRANGEMENTS, ACCORDING TO THE NEW PACKAGE TRAVEL DIRECTIVE - Masseno, Manuel David (Revista Direitos Emergentes na Sociedade Global, 2017)
.